2018
DOI: 10.1101/357293
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reactivation of TAp73 tumor suppressor by protoporphyrin IX, a metabolite of aminolevulinic acid, induces apoptosis in TP53-deficient cancer cells

Abstract: The p73 protein is a tumor suppressor that shares structural and functional similarity with p53. p73 is expressed in two major isoforms; the TA isoform that interacts with p53 pathway, thus acting as tumor suppressor and the N-terminal truncated ΔN isoform that inhibits TAp73 and p53 and thus, acts as an oncogene. By employing a drug repurposing approach, we found that protoporphyrin IX (PpIX), a metabolite of aminolevulinic acid (ALA) applied in photodynamic therapy of cancer, stabilizes TAp73 and activates T… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…It has been demonstrated that PpIX reactivates TAp73 tumor suppressor and induces TAp73-dependent apoptosis in TP 53-null cancer cells[17]. To assess if the growth inhibition observed in PDAC cell lines by PpIX and BPD is a result of apoptosis, we evaluated the expression of TAp73 and its pro-apoptotic targets in two pancreatic cancer cells lines.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that PpIX reactivates TAp73 tumor suppressor and induces TAp73-dependent apoptosis in TP 53-null cancer cells[17]. To assess if the growth inhibition observed in PDAC cell lines by PpIX and BPD is a result of apoptosis, we evaluated the expression of TAp73 and its pro-apoptotic targets in two pancreatic cancer cells lines.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown in a drug-repurposing approach that PpIX re-activates wild-type p53 and TAp73 and induces apoptosis in cancer cells. The mechanism is via inhibition of p53/MDM2 and TAp73/MDM2(X) interactions[16, 17]. Next, PpIX was identified in the in vitro screening as a potent, competitive inhibitor of thioredoxin reductase (TrxR)[25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…p53 acts together with p73 and p63 proteins in tumor suppression 4 . In addition to p53, exo-PpIX activates p73 by binding to N-terminal domain and inhibits the p73/ MDM2 and p73/MDMX interactions 16 . In our recent work in Cell Death Discovery, we confirmed that both p53 and p73 were activated by exo-PpIX in B-CLL cells.…”
Section: The P53/mdm2/mdmx-targeted Therapiesa Clinical Synopsismentioning
confidence: 99%
“…Next, it was shown that PpIX stabilizes TAp73 protein levels in p53-null cancer cells, induces TAp73-dependent transcription and activates apoptotic NOXA and PUMA. Also, PpIX ablated MDM2/MDMX/p73/ITCH complex and inhibited tumor growth of p53-null subcutaneous xenografts via activation of TAp73 and Poly (ADP-ribose) polymerase (PARP) cleavage [144] (Figure 4).…”
Section: Repurposed Drugs That Reactivate P53 and P73mentioning
confidence: 99%